Diosgenin and 5-Methoxypsoralen Ameliorate Insulin Resistance through ER-α/PI3K/Akt-Signaling Pathways in HepG2 Cells. (31st August 2016) - Fang, Ke; Dong, Hui; Jiang, Shujun; Li, Fen; Wang, Dingkun; Yang, Desen; Gong, Jing; Huang, Wenya; Lu, Fuer
Abstract : To determine the effects and the underlying mechanism of diosgenin (DSG) and 5-methoxypsoralen (5-MOP), two main active components in the classical Chinese prescription Hu-Lu-Ba-Wan (HLBW), on insulin resistance, HepG2 cells were incubated in medium containing insulin. Treatments with DSG, 5-MOP, and their combination were performed, respectively. The result showed that the incubation of HepG2 cells with high concentration insulin markedly decreased glucose consumption and glycogen synthesis. However, treatment with DSG, 5-MOP, or their combination significantly reversed the condition and increased the phosphorylated expression of estrogen receptor- α (ER α ), sarcoma (Src), Akt/protein kinase B, glycogen synthase kinase-3 β (GSK-3 β ), and the p85 regulatory subunit of phosphatidylinositol 3-kinase p85 (PI3Kp85). At the transcriptional level, expression of the genes mentioned above also increased except for the negative regulation of GSK-3 β mRNA. The increased expression of glucose transport-4 (GLUT-4) was meanwhile observed through immunofluorescence. Nevertheless, the synergistic effect of DSG and 5-MOP on improving glycometabolism was not obvious in the present study. These results suggested that DSG and 5-MOP may improve insulin resistance through an ER-mediated PI3K/Akt activation pathway which may be a new strategy for type 2 diabetes mellitus, especially for women in an estrogen-deficient condition.